Effect of cooling rate on phosphorus segregation behavior and the corresponding precipitation of γ″ and γ′ phases in IN718 alloy. Issue 7 (July 2019) - Zhang, Anwen; Zhang, Sha; Liu, Fang; Qi, Feng; Yao, Xiaoyu; Tan, Yuanguo; Jia, Dan; Sun, Wenru
Graphical abstract: Abstract: Effect of segregation behaviors of P at different cooling rates on the precipitation of γ″ and γ′ phases and the corresponding strength are investigated. The precipitation of γ″ and γ′ phases during cooling is sensitive to P concentration. With increasing the concentration of P, the amount of γ″ and γ′ particles increases after air cooling. With decreasing the cooling rate, the accelerating effect of P on the precipitation of γ″ and γ′ phases decreased first and then increased, which demonstrates the concentration of P dissolved in the grain interior decreases first and then increases. The different effects of P on γ″ and γ′ phases with different cooling rates were analyzed by the kinetic characteristic of nonequilibrium grain-boundary segregation. The characteristic of nonequilibrium grain-boundary segregation of P in superalloy is further confirmed, and the phenomenon caused by critical cooling rate is captured.